Pendampingan UMKM dalam Pendaftaran NIB melalui sistem OSS (Online Single Submission) sebagai Langkah Strategis Menuju Kemandirian dan Keberlanjutan Usaha di Kota Kediri - Damayanti, Elvina; Chanifah, Diva Nur; Pricellia, Sonia Tiffanny; Setianingsih, Rizqi Mei; Ramadhani, Theanna Dwi; Tyas, Erika Puspita Febrining; Ningrum, Anita Sekar Ayu; Istianatillah, Tahkta; Sugiarto, Suprihantosa (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Business Identification Number (BIN) is an official identity that must be owned by Micro, Small, and Medium Enterprises (MSMEs) to carry out business activities legally in accordance with the provisions of laws and regulations. In Kediri City, although the number of MSMEs continues to increase, many business actors do not yet understand the importance of having a NIB as a form of business legality. This community service activity aims to provide understanding and assistance to MSME actors regarding the creation of BIN through the OSS (Online Single Submission) system. The method used is assistance. The results of the activity show that this assistance is effective in increasing the knowledge and awareness of MSME actors regarding the benefits of business legality, such as easy access to financing, marketing opportunities, and legal protection. With the BIN, MSMEs in Kediri City can run their businesses in a more focused, sustainable, and competitive manner.